Hospodářské barometry - teorie a praxe - Souček, Eduard (Univerzita Pardubice, 1999)
Judgement is a major factor predicting changes or turns in the behaviour of economic activity. In predicting economic changes is necessary to establish judgement with specific indicator which have association with the variable to forecast. In article is described leading economic indicator approach as possible solution of the construction some of the "barometer economic activity". The problems are discussed with respect to the conditions of Czech Republic.
Keywords: Ekonomika; ekonomický vývoj; prognostika; ukazatele